2019
DOI: 10.1002/col.22361
|View full text |Cite
|
Sign up to set email alerts
|

Reflective color reduction using genetic algorithm optimization

Abstract: A subset of colors often needs to be selected to represent a full set. In one such application, a multi‐band color sensor is used to measure reflective color samples, and a matrix transformation method is used to recover the reflectance spectrum of the measured sample. To achieve this, a group of training colors needs to be selected to calculate the transformation matrix. A genetic algorithm (GA) has been developed to optimize the selection of the subset of training colors, and the result is compared with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Many color reduction methods are established necessarily based on data clustering algorithms 37,38 . In Celebi, 39 the improvement of the K‐means clustering algorithm in the color reduction of color images showed that this algorithm is criticized in the color reduction literature due to its very high computational requirements and dependence on initial values.…”
Section: Related Workmentioning
confidence: 99%
“…Many color reduction methods are established necessarily based on data clustering algorithms 37,38 . In Celebi, 39 the improvement of the K‐means clustering algorithm in the color reduction of color images showed that this algorithm is criticized in the color reduction literature due to its very high computational requirements and dependence on initial values.…”
Section: Related Workmentioning
confidence: 99%